Multiple Layered Control of the Conjugation Process of the Bacillus subtilis Plasmid pLS20 - Meijer, Wilfried J. J.; Boer, D. Roeland; Ares, Saúl; Alfonso, Carlos; Rojo, Fernando; Luque-Ortega, Juan R.; Wu, Ling Juan (Frontiers in Molecular Biosciences, 2021)
Bacterial conjugation is the main horizontal gene transfer route responsible for the spread of antibiotic resistance, virulence and toxin genes. During conjugation, DNA is transferred from a donor to a recipient cell via a sophisticated channel connecting the two cells. Conjugation not only affects many different aspects of the plasmid and the host, ranging from the properties of the membrane and the cell surface of the donor, to other developmental processes such as competence, it probably also poses a burden on the donor cell due to the expression of the large number of genes involved in the conjugation process. Therefore, expression of the conjugation genes must be strictly controlled. Over the last decade, the regulation of the conjugation genes present on the conjugative Bacillus subtilis plasmid pLS20 has been studied using a variety of methods including genetic, biochemical, biophysical and structural approaches. This review focuses on the interplay between RcopLS20, RappLS20 and Phr*pLS20, the proteins that control the activity of the main conjugation promoter Pc located upstream of the conjugation operon. Proper expression of the conjugation genes requires the following two fundamental elements. First, conjugation is repressed by default and an intercellular quorum-signaling system is used to sense conditions favorable for conjugation. Second, different layers of regulation act together to repress the Pc promoter in a strict manner but allowing rapid activation. During conjugation, ssDNA is exported from the cell by a membrane-embedded DNA translocation machine. Another membrane-embedded DNA translocation machine imports ssDNA in competent cells. Evidences are reviewed indicating that conjugation and competence are probably mutually exclusive processes. Some of the questions that remain unanswered are discussed.